Technology Compatibility and Social Support: Determinants of Students' Self-Regulated Learning in the Digital Era - Laka, Laurensius; Krismiyanto, Alfonsus; Jona, Marieta (Kuras Institute, 2025)
Education was regarded as a long-term investment to develop superior human resources. Unfortunately, the education system in Indonesia remained overshadowed by inequality and systemic obsolescence, making the reinforcement of self-regulated learning (SRL) as the foundation of students’ learning autonomy urgently necessary. The objective of this study was to investigate the impact of Technology Compatibility and Social Support on the SRL of students at Catholic Senior High School Bhakti Luhur Malang, Indonesia. Employing a quantitative approach, data were collected from 144 students selected through a stratified random sampling technique. The research instrument consisted of questionnaires for the three measured constructs, all of which had been validated in advance. Multiple linear regression analysis was conducted using SPSS software. The results revealed that the correlation coefficient between the independent and dependent variables was r = 0.786, indicating a strong relationship. In terms of causality, the simultaneous regression analysis yielded p = 0.001 < 0.05, suggesting that the regression model was appropriate for predicting students' SRL. Furthermore, the variables of Technology Compatibility and Social Support were found to significantly affect SRL individually, with each showing a p = 0.001. Therefore, both simultaneously and individually, the two independent variables significantly influenced students’ SRL, with Social Support contributing more than Technology Compatibility.